1987
DOI: 10.1128/jb.169.1.205-209.1987
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of pyrroloquinoline quinone-dependent D-glucose oxidase respiratory chain of Escherichia coli with cytochrome o oxidase

Abstract: D-Glucose dehydrogenase is a pyrroloquinoline quinone-dependent primary dehydrogenase linked to the respiratory chain of a wide variety of bacteria. The enzyme exists in the membranes of Escherichia coli, mainly as an apoenzyme which can be activated by the addition of pyrroloquinoline quinone and magnesium. Thus, membrane vesicles of E. coli can oxidize D-glucose to gluconate and generate an electrochemical proton gradient in the presence of pyrroloquinoline quinone. The D-glucose oxidase-respiratory chain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 25 publications
(23 reference statements)
3
34
0
1
Order By: Relevance
“…Using the holo-enzyme thus prepared, the following enzyme activities were measured. PMS reductase activity was measured spectrophotometrically (U-2000A, Hitachi) with PMS and 2,4-dichlorophenol indophenol as an electron mediator and acceptor, respectively, as described previously (13,15). UQ 2 reductase activity was also measured spectrophotometrically in the presence of 0.025% Tween 20 (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the holo-enzyme thus prepared, the following enzyme activities were measured. PMS reductase activity was measured spectrophotometrically (U-2000A, Hitachi) with PMS and 2,4-dichlorophenol indophenol as an electron mediator and acceptor, respectively, as described previously (13,15). UQ 2 reductase activity was also measured spectrophotometrically in the presence of 0.025% Tween 20 (24).…”
Section: Methodsmentioning
confidence: 99%
“…coli membrane-bound mGDH, which is known as a quinoprotein, catalyzes the oxidation of D-glucose to D-gluconate at the periplasmic side to feed electrons to ubiquinol oxidase via UQ in the respiratory chain (13)(14)(15). Topological analysis of mGDH revealed a unique structure consisting of an N-terminal hydrophobic domain with five membrane-spanning segments and a large C-terminal domain residing in the periplasm (15), which contains PQQ as a coenzyme and Ca 2ϩ -or Mg 2ϩ -binding sites in a superbarrel structure, conserved in quinoproteins (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The Escherichia coli membrane-bound glucose dehydrogenase (mGDH) 2 belongs to the quinoprotein family with PQQ as a coenzyme (1,2), and it catalyzes D-glucose oxidation to D-gluconate at the periplasmic side to transfer electrons to ubiquinol oxidase via UQ in the respiratory chain (3)(4)(5). Topological analysis revealed that mGDH consists of an N-terminal hydrophobic domain with five membrane-spanning segments and a large C-terminal domain residing in the periplasm, which contains PQQ and Ca 2ϩ -or Mg 2ϩ -binding sites in a superbarrel structure, conserved in quinoproteins (6 -8).…”
mentioning
confidence: 99%
“…However, the biologically active pigment prodigiosin is inhibited by growth in glucose-rich medium (43). Quinoprotein glucose dehydrogenase uses PQQ as a cofactor, and its substrates are D-glucose and ubiquinone, a component of the electron transport chain (44,45). S. marcescens glucose dehydrogenase (GdhS) was previously shown to require PQQ for glucose dehydrogenase activity (46).…”
mentioning
confidence: 99%